Clinical, Ultrasonographic and Haemato-Biochemical Assessment of Liver and Gall Bladder Affections in Dogs - Patel, Malhar D.; Parikh, Pinesh V.; Barot, Hiren M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A total of 109 dogs were screened, of which 30 dogs with hepatobiliary affections were included for this study. Common clinical findings in hepatobiliary disease were intermittent anorexia, lethargy, weight loss, and vomiting. Ultrasonographic examination showed reduced parenchymal echogenicity with prominent visualization of hepatic vasculature in acute hepatitis; hyperechoic bright liver with normal size in chronic hepatitis and bright and small liver with irregular margins in hepatic cirrhosis. Hepatomegaly on ultrasonography appeared as enlarged liver with rounded margins. Further ascites, hepatic cyst, hepatic neoplasia, cholelith, and gall bladder polyp/mass were diagnosed by using ultrasonography. Based on present findings, it was concluded that ultrasonography could be best exploited in hepatobiliary disorders.